2016
DOI: 10.1002/art.39739
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 3 Inhibits Osteoarthritis Progression in the Knee Joints of Adult Mice

Abstract: Our findings indicate that FGFR-3 delays OA progression in mouse knee joints at least in part via down-regulation of IHH signaling in articular chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…Interestingly, recent studies on mice have indicated that the FGFR3-mutation might protect from the development of arthritis in achondroplasia. 59 Two studies reported on osteopenia in achondroplasia, 17,19 but the studies are small and the findings need to be confirmed in future studies.…”
Section: Medical Complications Health Characteristics and Psychosomentioning
confidence: 97%
“…Interestingly, recent studies on mice have indicated that the FGFR3-mutation might protect from the development of arthritis in achondroplasia. 59 Two studies reported on osteopenia in achondroplasia, 17,19 but the studies are small and the findings need to be confirmed in future studies.…”
Section: Medical Complications Health Characteristics and Psychosomentioning
confidence: 97%
“…Sh3bp4 thus represents a new osteoarthritis susceptibility gene, the deletion of which accelerates joint damage. Its role in disease pathogenesis may involve the key TfR, FGFR, mTOR and Wnt signalling pathways, which regulate bone and cartilage homeostasis and tissue repair [47][48][49][50] .…”
Section: Early Onset Osteoarthritis In Bhlhe40 -/And Sh3pb4 -/Mutant mentioning
confidence: 99%
“…Valverde‐Franco et al showed that the absence of FGFR3 signaling in the joints of Fgfr3 −/− mice led to premature cartilage degeneration and early arthritis. Recently, Tang et al indicated that adult mice carrying conditional Fgfr3 deletion in chondrocytes caused aggravated cartilage degeneration after OA‐induced surgery. Conversely, chondrocyte‐specific Fgfr3 activation ameliorated cartilage degeneration via downregulation of Indian hedgehog signaling in articular chondrocytes …”
mentioning
confidence: 99%